Sorption isotherms of alligator's meat (Caiman crocodilus yacare) - Lopes, J. F.; Romanelli, P. F.; Barboza, SHR; Gabas, A. L.; Telis-Romero, J. (Elsevier B.V., 2002)
Sorption isotherms were determined for salted alligator's meat at four different temperatures (10degreesC, 15degreesC, 25degreesC and 35degreesC), using a standard gravimetric method. The goodness of fit of five sorption models to experimental data was determined. Five models, namely the GAB, the BET, the Halsey, the Henderson and the Hailwood and Horrobin, were evaluated to determine the best fit for the experimental data. The GAB was the best fitted model for the data of salted alligator's meat with an average error less than 10% for temperature of 10degreesC and less than 5% for the others temperatures. The coefficients of determination (r(2)) were 0.99 for all temperatures considered. The monolayer values decreased as temperature increased. The other four models were not appropriated to fit the data because of the high error values, although the r(2) were also similar to the GAB model. The net isosteric heat of sorption was estimated from equilibrium sorption data, using the Clausis-Clapeyron equation. Isosteric heats of sorption were found to increase with increasing temperature and could be well adjusted by an exponential relationship. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: isotherms; moisture content; alligator's meat